Penerapan Etika Bisnis Islam dalam Membangun Kepercayaan dan Loyalitas Konsumen: Studi pada Toko Dwi.chyanti Fashion di Facebook - Nursalamah (BUGIS : Journal of Business, Technology, & Social Science, 2025)
The development of digital technology has brought significant changes to the world of trade, including in Indonesia. The emergence of online trading platforms (e-commerce) allows traders to offer products more widely and efficiently. In the rapid growth of the digital era, social media platforms such as facebook have become one of the main tools for business actors in marketing their products and services. Social media not only functions as a means of promotion, but also as a medium for building interactions with consumers. One example of the application of this principle can be seen in the Dwi.chyanti fashion store, an online business that is active on Facebook. This study aims to analyze the success of the Dwi.chyanti fashion store in building consumer trust and loyalty through the application of professional ethics based on the principles of Islamic business ethics. In the context of Dwi.chyanti Fashion Store, this study not only emphasizes the application of professional ethics, but also its impact on consumer perception and business success in maintaining customer loyalty.